The combination of hot water spray and subzero saline chilling improved chilling efficiency, meat quality, and sensory attributes - K. Kawamura; D. Ma; D.U. Ahn; H.-S. Seo; V. Hogan; L.N. Stephens; J. Moallem; J.W. Jin; I. Kang (Journal of Applied Poultry Research)
Summary: Accelerated poultry processing is always desirable when the product quality, visual appearance, and sensory attributes are the same or better than the conventional processing. This research evaluated the effects of subzero saline chilling (SSC) with or without hot water spray (HWS) on broiler carcasses to improve chilling efficiency, carcass quality, and sensory attributes. Eviscerated broiler carcasses were subjected to one of the six chilling methods with or without HWS for 1 min as follows: 1) Water immersion chilling at 0.5 °C (WIC), 2) WIC after HWS at 68 °C for 1 min (WIC-HWS 68), 3) WIC after HWS at 71 °C for 1 min (WIC-HWS 71), 4) Subzero saline chilling at 4% NaCl/-2.41 °C (SSC), 5) SSC after HWS at 68 °C for 1 min (SSC-HWS 68), 6) SSC after HWS at 71 °C for 1 min (WIC-HWS 71). The SSC showed shorter chilling time than other treatments. The fillets from the SSC and SSC-HWS were more tenderized than the WIC and WIC-HWS, regardless of the HWS exposure. HWS treatments showed higher lightness values (or partially cooked appearance) than WIC and SSC. Significantly lower redness (a*) values were observed in the SSC68 and SSC71 than in the remaining treatments, except the WIC68. In the consumer panel, the carcass fillets from SSC-HWS showed higher hedonic scores than WIC and WIC-HWS for flavor, juiciness, tenderness, saltness, and overall acceptance, with an intermediate score observed for SSC in tenderness and juiciness. In descriptive sensory analysis, the fillets from SSC, WIC and SSC-HWS were rated less intense for bloody and cardboardy attributes than WIC-HWS. Based on those results, the combination of SSC-HWS improved meat tenderness and sensory attributes over the control, while the SSC improved chilling efficiency among all treatments.